A multiobjective model for distribution system planning based on tabu search - Pereira, Benvindo Rodrigues [UNESP]; Mantovani, Jose Roberto Sanches [UNESP]; Cossi, Antonio Marcos [UNESP]; Contreras, Javier (Institute of Electrical and Electronics Engineers (IEEE), 2013)
This paper presents a multiobjective model for the multistage planning problem of a distribution system. The problem is formulated as a multiobjective mixed integer nonlinear programming model. The actions deemed in this model for each period of the planning horizon are: increase in the capacity of existing substations (or construction of new ones), exchange of cables in existing lines (and construction of new feeders), reconfiguration of the network, allocation of sectionalizing switches and construction of tie lines. Taking into account these actions, the objective functions used in this model are the investment and operational costs as well as the system's reliability under contingencies using an n-1 criterion. Reliability is calculated by means of the non-supplied energy. To solve the proposed multiobjective model a multiobjective tabu search method is used. Numerical results are presented for a 54-bus system. © 2013 IEEE.
Keywords: Distribution system planning; multiobjective optimization; reliability; tabu search